ANALISIS PENDAPATAN USAHATANI JAGUNG PIPIL DALAM PROGRAM CONTRACT FARMING DI DESA RARAMPADENDE, KECAMATAN DOLO BARAT, KABUPATEN SIGI - Antero, M; Dulbari, Dulbari; Pujiana, Tri (PLANTKLOPEDIA: Jurnal Sains dan Teknologi Pertanian, 2025)
This study aims to analyze the income of corn farming in the contract farming program in Rarampadende Village, Dolo Barat District, Sigi Regency. The method used is a descriptive quantitative approach with primary data collection through questionnaires and interviews, as well as secondary data from official documentation. The analysis includes the calculation of farming income, R/C ratio, and B/C ratio. The results showed that the average farmer income was IDR15.935.000,00 per hectare per planting season. The average R/C ratio of 3,05 indicates that every IDR1,00 of production costs generates an income of IDR3,05; while the average B/C ratio of 2,05 indicates that every IDR1,00 of production costs generates a profit of IDR2,05. This shows that corn farming in this program is profitable. The main obstacles in this program are dependence on partner companies, price gaps, and limited access to technical training.